Analisis Pengaruh E-Service Quality Dan Perceived Value Terhadap Kepuasan Pelanggan Dan Loyalitas Pelanggan Layanan Internet Indihome - Lia Arisyanti Ndun (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
The purpose of this study was to analyze the effect of e-service quality and perceived value towards customer satisfaction and its impact towards customer loyalty for IndiHome customers and internet service customers. Using random sampling technique, the questionnaire was well-collected and was used in data processing using the Structural Equation Modeling (SEM) method with the Smart PLS program. This analysis was conducted on 135 respondents as customers of IndiHome's internet service. Variables that are used in this study were e-service quality, perceived value, customer satisfaction and customer loyalty. Based on the results of the study, it was found that e-service quality and perceived value have influence towards customer satisfaction, customer satisfaction have strong influence towards customer loyalty, yet e-service quality and perceived value have weak indirect influence towards customer loyalty.